Three-Dimensional Human Skin Models to Understand Staphylococcus aureus Skin Colonization and Infection - Popov, Lauren; Kovalski, Joanna; Grandi, Guido; Bagnoli, Fabio; Amieva, Manuel R. (Frontiers in Immunology, 2014)
Staphylococcus aureus is both a major bacterial pathogen as well as a common member of the human skin microbiota. Due to its widespread prevalence as an asymptomatic skin colonizer and its importance as a source of skin and soft tissue infections, an improved understanding of how S. aureus attaches to, grows within, and breaches the stratified layers of the epidermis is of critical importance. Three-dimensional organotypic human skin culture models are informative and tractable experimental systems for future investigations of the interactions between S. aureus and the multifaceted skin tissue. We propose that S. aureus virulence factors, primarily appreciated for their role in pathogenesis of invasive infections, play alternative roles in promoting asymptomatic bacterial growth within the skin. Experimental manipulations of these cultures will provide insight into the many poorly understood molecular interactions occurring at the interface between S. aureus and stratified human skin tissue.